The Effectiveness of Self-Care in Diabetics on Self-Insulin Administration and Behavioral Markers Among Adolescents with Type 1 Diabetes - Ochappan Selvarajan; Kannan Rajendran; A. Helen Mary Perdita (Journal of Pharmacy and Bioallied Sciences)
Background: Diabetes mellitus is a long-term, progressive metabolic disease that is primarily caused by an absolute type 1 diabetes or relative type 2 diabetes, which lacks the hormone insulin. Diabetes education is essential, but patients must fully realize its benefits through action or self-care activities. Objectives: The objective of the study is to evaluate the effectiveness of self-care in diabetics on self-insulin administration and behavioral markers among adolescents with type I diabetes. Methods: This study adopted quantitative research methodology, utilizing a true experimental research design with pretest and post-test phases. Power analysis was used to calculate the study sample of 105 per group. The total sample size of the study is 210; the experimental group consists of 105 members, while the control group consists of 105 members. The study was conducted from 21.12.2022 till 22.03.2023. We assessed insulin administration knowledge through a self-structured questionnaire and level of depression by using the WHO Wellbeing Scale. Levels of anxiety were measured by using the Hospital anxiety and depression scale. After the intervention, post-test 1 was conducted at the end of 13 weeks and post-test 2 was conducted after 25 weeks. Results: The study revealed a significant difference in the scores for insulin administration, depression, and anxiety levels between the pretest, post-test 1, and post-test 2 in the experimental group (P < 0.001). In contrast, the control group showed no statistical differences across these time points. Conclusion: The study concluded that self-care in diabetics successfully improved the knowledge of insulin administration, reduced anxiety levels, and decreased depression in adolescents diagnosed with type I diabetes.